(untitled) (Journal of research in medical and health sciences, 2026)
The paper constructs an integrative biopsychological theoretical framework for dance education promoting adolescent physical and mental health. The research proposes that dance, integrating the three attributes of rhythmic movement, emotional expression, and social interaction, serves as an "ideal perturbation source" for regulating the neuro-endocrine-immune network. Its core mechanism lies in achieving a paradigm shift from "stress reduction" to "growth promotion," simultaneously inhibiting excessive stress-immunosuppression pathways and activating growth-immunoenhancement pathways. Theoretical deduction indicates that dance optimizes autonomic nervous system balance, shapes an internal environment supportive of positive emotions and neural plasticity, and enhances immune homeostasis via psychoneuroimmunological pathways. Dance also proactively reconstructs positive emotions through body postures and strengthens the neural foundations of self-efficacy and social belonging. Ultimately, a "Body-Mind Resonance Spiral" model is formed, elucidating how physiological optimization and psychological experiences mutually promote each other, creating a positive feedback loop. This study demonstrates the fundamental constructive value of dance education in adolescent development, providing an interdisciplinary explanation for the public health significance of arts education.